Σ‐Noninnocence: Masked Phenyl‐Cation Transfer at Formal NiIV. Issue 37 (15th July 2019) - Steen, Jelte S.; Knizia, Gerald; Klein, Johannes E. M. N.
Abstract: Reductive elimination is an elementary organometallic reaction step involving a formal oxidation state change of −2 at a transition‐metal center. For a series of formal high‐valent Ni IV complexes, aryl–CF3 bond‐forming reductive elimination was reported to occur readily (Bour et al. J. Am. Chem. Soc . 2015, 137, 8034–8037). We report a computational analysis of this reaction and find that, unexpectedly, the formal Ni IV centers are better described as approaching a +II oxidation state, originating from highly covalent metal–ligand bonds, a phenomenon attributable to σ‐noninnocence. A direct consequence is that the elimination of aryl–CF3 products occurs in an essentially redox‐neutral fashion, as opposed to a reductive elimination. This is supported by an electron flow analysis which shows that an anionic CF3 group is transferred to an electrophilic aryl group. The uncovered role of σ‐noninnocence in metal–ligand bonding, and of an essentially redox‐neutral elimination as an elementary organometallic reaction step, may constitute concepts of broad relevance to organometallic chemistry. Abstract : Oxidation state? Using computational analysis, it is shown that formal Ni IV centers in high‐valent complexes performing aryl–CF3 bond‐forming reductive eliminations are better described as approaching a +II oxidation state and that the elimination is essentially redox‐neutral. This originates from highly covalent metal–ligand bonds and is attributable to σ‐noninnocence.